Changing Livelihoods in Rural Eastern Cape, South Africa (2002–2016): Diminishing Employment and Expanding Social Protection. Issue 4 (18th July 2020) - Hajdu, Flora; Neves, David; Granlund, Stefan
Abstract : Despite long-standing patterns of agrarian change in South and Southern Africa, rural locales remain home to millions of people, characterised by widespread poverty and vulnerability. This is evident in South Africa's former 'homelands', the site where this study examined changes in rural livelihoods over a 14-year period. Detailed survey data (collected in 2002 and 2016) from two villages in the Pondoland region of Eastern Cape province, and augmented by in-depth fieldwork, are analysed to explore the drivers of contemporary livelihood change. Key livelihood activities are examined, namely paid employment, social grant receipt, horticulture and livestock production, marine-resource and firewood harvesting. So too are changes within, and between, these diverse livelihood activities over time. Both monetised (income-earning) activities, and 'unremunerated' or unmonetised activities (for example, subsistence agriculture or marine-resource harvesting) are measured, aggregated and compared, in order to consider the drivers, consequences and prospective future trajectories of livelihood change. Key findings for impoverished households in the villages are that waged work has decreased significantly, while expanding social welfare provision has prevented plunges into deeper poverty. Agriculture and marine-resource harvesting remain dynamic, albeit unevenly engaged in by villagers. Amid these larger patterns, local-level variations are evident, with discrepant employment and agricultural production patterns across villages. The role of the state is ambiguous, being both a restrictor and enabler of local livelihoods. As jobs and other livelihood opportunities diminish, the villagers express frustration with the state, but remain simultaneously heavily reliant on state fiscal transfers, through grants and public employment schemes. The findings speak not only to the dynamics of rural livelihoods in South Africa's former homelands; they also point to changes in rural dwellers' livelihoods, within contexts of agrarian change, rural dispossession, inequality and receding prospects for employment, increasingly evident across the global south.